Wheat bran arabinoxylans in breadmaking : their effect on staling and other quality aspects - Henriksson, Ylva (SLU/Department of Molecular Sciences, 2020)
In the face of agriculture-related global challenges, there is a need to produce food more efficiently and effectively, reduce food waste and increase utilization of agricultural by-products such as wheat bran. Extracted arabinoxylans from wheat bran have previously been found to retard staling and thus extend shelf life of bread. The purpose of this study was therefore to investigate the effect of addition of 0.3, 1.0 and 1.7 % of three arabinoxylan fractions (extract, feruloylated and unferuloylated arabinoxylan) on dough and bread quality aspects and on staling, to evaluate the fractions in terms of their potential as bread improvers, and to determine whether arabinoxylan addition influences consumer acceptance of fresh and stored bread. Breads were made with each arabinoxylan fraction and addition level combination. Dough and bread quality aspects were determined on the baking day. Staling-related parameters were measured after 1, 7 and 14 days of storage. Bread quality aspects were largely unaffected by arabinoxylan addition. Some positive effect on textural parameters during storage were observed. The main difference between the fractions was their effect on baking absorption and crumb moisture content. In the consumer acceptance test, arabinoxylan addition did not significantly influence acceptance of fresh or stored breads. All three arabinoxylan fractions have potential as bread improvers to retard staling while maintaining quality. However, the overall lack of significant results in this study calls for further research to elucidate the future role of wheat bran arabinoxylans in industrial breadmaking.